2019
DOI: 10.1097/md.0000000000017370
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of postoperative survival of triple-negative breast cancer based on nomogram model combined with expression of HIF-1α and c-myc

Abstract: The aims of this study were to explore the expression of hypoxia inducible factor-1α (HIF-1α) and c-myc protein in triple-negative breast cancer (TNBC) and its clinical prognostic significance, and to establish a prediction model for postoperative survival of TNBC based on nomogram.A total of 87 patients with TNBC at the Department of Breast Surgery, Beijing Chaoyang Hospital, Capital Medical University from January 2012 to December 2015 were enrolled in this study. Immunohistochemistry was performed to detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
(22 reference statements)
1
12
0
Order By: Relevance
“…High MYC level was significantly associated with stabilized HIF1α expression in various cancers, such as prostate cancer, triple-negative breast cancer (TNBC) and animal model of CNS primitive neuroectodermal tumors (Malchenko et al, 2017;Boldrini et al, 2019;Cui and Jiang, 2019). Deregulated MYC cooperates with HIFs to regulate cancer cell adaptation to hypoxia, rewire metabolism, and promote angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High MYC level was significantly associated with stabilized HIF1α expression in various cancers, such as prostate cancer, triple-negative breast cancer (TNBC) and animal model of CNS primitive neuroectodermal tumors (Malchenko et al, 2017;Boldrini et al, 2019;Cui and Jiang, 2019). Deregulated MYC cooperates with HIFs to regulate cancer cell adaptation to hypoxia, rewire metabolism, and promote angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Deregulated MYC cooperates with HIFs to regulate cancer cell adaptation to hypoxia, rewire metabolism, and promote angiogenesis. Also, high MYC and HIF expression is associated with poor outcome in various cancers such as prostate and breast cancers and clear cell renal cell carcinomas (Maroto et al, 2017;Boldrini et al, 2019;Cui and Jiang, 2019). Therefore, MYC and HIFs are potential biomarkers for targeting both pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Although the complexities of cancer prognosis (the high variability of tumor mutations, histological types, grades and stages) makes it too simplistic to think that the levels of expression of a single gene such as HIF1A might have significant impact on prognosis, increased HIF-1α and HIF-2α protein levels in diagnostic tumor biopsies have been correlated with poor prognosis in other types of cancer also, such as brain, breast, colon, cervix, endometrium, head/neck, lung, ovary, pancreas, prostate, rectum and stomach (reviewed in [1]). More recently, high HIF-1α expression has been studied in triple-negative breast cancer (TNBC) [73]. TNBC are a heterogeneous group of poorly differentiated, highly aggressive and metastatic breast cancer type.…”
Section: Association Of Hif-1 Expression and Cancer Prognosismentioning
confidence: 99%
“…They lack specific molecular-targeted therapy and there is an urgent need to find effective biomarkers rather than relying of their lack of hormone receptors and Her2 expression to define this subgroup. These authors [73] found that HIF-1α and c-Myc expression detected by immunohistochemistry could add to the development of a prognostic nomogram including histological grade and stage of cancer (based on tumor size (T), lymph node involvement (N) and distant metastases (M), known as TNM status). In an effort to validate the proposed nomogram in our institution, we are currently evaluating the feasibility of including HIF-1α immunohistochemistry in the biomarker profile ( Figure 2).…”
Section: Association Of Hif-1 Expression and Cancer Prognosismentioning
confidence: 99%
“…To date, nomogram predictions for the survival of TNBCs merely considered conventional clinical and pathological risk factors [ 8 – 10 ]. While efforts have been made in adding novel prognostic factors such as the expression of HIF-1 α and c-myc to nomograms [ 11 ], imaging features have not yet been analyzed. Nowadays, the advent of deep-learning-based “radiomics” technology has allowed for the high-throughput extraction of quantitative imaging features from images, thus enhancing the accuracy of diagnosis and prognostic prediction, especially for malignancies [ 12 ].…”
Section: Introductionmentioning
confidence: 99%